Drone image-based parameters for assessing the vegetation condition the reclamation success in post-mining oil exploration - Tirta Negara; I Nengah Surati Jaya; Cecep Kusmana; Irdika Mansur; Nitya Ade Santi (Universitas Ahmad Dahlan, 2021)
This paper examines drone-based parameters for assessing the success of reclamation activities in post-mining oil-exploration area. The applied drone-based images were multispectral images having visible light and infrared wavelength regions with 5 cm spatial resolution. The main objective of the study is to develop a mathematical model to estimate a reclamation success, through development of success indices. The model were developed by analyzing the relationship between the vegetation success and the digital number values of original and/or synthetic images of drone-based images using 70 sample plots. The mathematical models were developed using a regression analysis, where responses are biomass, volume, and basal area, while the independent variables were original digital number value of images and their derivative synthetic images. The study found that there is a close relationship between parameter biomass stock (ton/ha) and basal area (cm) with both, i.e., original digital number and vegetation indices.